2021
DOI: 10.1002/cpz1.251
|View full text |Cite
|
Sign up to set email alerts
|

Critical Conditions for Studying Interleukin‐11 Signaling In Vitro and Avoiding Experimental Artefacts

Abstract: Interleukin (IL) 11 is a member of the IL6 family of cytokines which require the ubiquitous gp130 receptor to activate canonical (JAK/STAT) and non-canonical (e.g., ERK) signaling pathways. The IL11 cytokine is upregulated in a number of fibro-inflammatory diseases and cancer, where it binds the cognate IL11 receptor alpha subunit (IL11RA) to form a hexameric IL11:IL11RA:gp130 signaling complex. The specific IL11RA receptor is highly expressed on cells of the stromal and parenchymal niche but expressed at low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…All cells were grown and maintained at 37 °C and 5% CO 2 . The culture of primary human hepatic stellate cells (HSCs) and primary human hepatocytes were described previously ( Viswanathan et al., 2021 ). Primary human cardiac fibroblasts (HCFs (52-year-old male), ScienCell) were grown and maintained in complete fibroblasts medium-2 (ScienCell) which contains 5% fetal bovine serum (FBS, ScienCell), 1% fibroblasts growth supplement-2 (FGS-2, ScienCell) and 1% penicillin-streptomycin (P/S, ScienCell).…”
Section: Methodsmentioning
confidence: 99%
“…All cells were grown and maintained at 37 °C and 5% CO 2 . The culture of primary human hepatic stellate cells (HSCs) and primary human hepatocytes were described previously ( Viswanathan et al., 2021 ). Primary human cardiac fibroblasts (HCFs (52-year-old male), ScienCell) were grown and maintained in complete fibroblasts medium-2 (ScienCell) which contains 5% fetal bovine serum (FBS, ScienCell), 1% fibroblasts growth supplement-2 (FGS-2, ScienCell) and 1% penicillin-streptomycin (P/S, ScienCell).…”
Section: Methodsmentioning
confidence: 99%
“…A critical difference being that the study by Zheng et al used an RSV enhancer-driven SV40 T antigen immortalised PSC-like cell line (HP-1) [ 27 ]. We have shown that high passage primary cells and immortalised cell lines have different/artefactual signalling and phenotypes, as compared to primary cells, when stimulated with IL6 family members [ 28 ]. We suggest that the data shown by Zheng et al are relevant to transformed HP-1 cells but not primary human PSCs.…”
Section: Discussionmentioning
confidence: 99%
“…IL11 is a member of the IL6 cytokine family, mainly derived from stromal cells such as fibroblasts [ 8 ]. In fibroblasts, IL11 signaling activates JAK/STAT3 and MEK/ERK via IL11RA/IL6ST and possibly AKT [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…IL11 is a member of the IL6 cytokine family, mainly derived from stromal cells such as fibroblasts [ 8 ]. The expression of IL11 promotes tissue fibrosis [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%